EKSPERIMENTASI MODEL PEMBELAJARAN THINK TALK WRITE (TTW) DAN NUMBERED HEAD TOGETHER (NHT) TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KONSEP DIRI BELAJAR MATEMATIKA SISWA DI SMP NEGERI E-KABUPATEN BLORA - Yekti Putri Kusumaningtyas; Tri Atmojo Kusmayadi; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research aimed to find out: (1) which one is better among learning models of Think Talk Write (TTW), Numbered Head Together (NHT) or conventional one in giving mathematics learning achievement, (2) which one is better among students’ levels of self concept, students having high, medium or low self concept in giving mathematics learning achievement. (3) in each learning model, which one is better among students’ levels of self concept in having mathematics learning achievement and (4) in each level of self concept, which one is better among Think Talk Write (TTW), Numbered Head Together (NHT) or conventional model in giving mathematics learning achievement. This research was the quasi-experimental research with 3×3 factorial design. The population of research was all students of Junior High School (SMP) in Blora. The samples were chosen by using stratified cluster random sampling. The samples were 309 students; consist of 105 students in the first experimental class, 105 in the second experimental class, and 99 students in control class. The instruments used to collect the data were the test of mathematics achievement and questionnaire of self concept. Pre-requisite tests were used Lilliefors method for normality test and Bartlett method for homogeneity test. After examining the data, it showed that the data had same variance and they were in normal distribution. Prior knowledge data are examined by using one-way ANOVA with unbalanced cells. It showed that three classes had balance prior knowledge. Meanwhile, the technique of analyzing the data was two-ways ANOVA with unbalanced cells. The result of research showed that: (1) Think Talk Write (TTW) and Numbered Head Together (NHT) learning models had better achievement than conventional model, Think Talk Write (TTW) and Numbered Head Together (NHT) learning models had the same mathematics achievement, (2) the students having high self concept had better learning achievement than those having medium and low self concept, the students having medium and low self concept had the same mathematics learning achievement, (3) in each learning model: the students having high self concept had better learning achievement than those having medium and low self concept, the students having medium and low self concept had the same mathematics learning achievement, (4) in each level of self concept: Think Talk Write (TTW) and Numbered Head Together (NHT) model better learning achievement than conventional model, Think Talk Write (TTW) and Numbered Head Together (NHT) model had the same good mathematics learning achievement.Keywords: Think Talk Write (TTW), Numbered Head Together (NHT), mathematics learning achievement, and self concept.